2017
DOI: 10.1039/c6sc05532j
|View full text |Cite
|
Sign up to set email alerts
|

Redox-active triazatruxene-based conjugated microporous polymers for high-performance supercapacitors

Abstract: A novel set of redox-active triazatruxene-based conjugated microporous polymers have been explored as efficient electrode materials for high-performance supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 54 publications
3
88
0
Order By: Relevance
“…Another promising strategy is to design porous polymeric frameworks with conducting properties as electrode materials for supercapacitors. The conductive frameworks enable the high utilization of the large surface area for electrical double layer capacitance and heteroatom effect (N) for pseudocapacitance, as has been found in aza‐fused CMPs (Figure g), triazatruxene‐based microporous polymers (Figure h), and triazine‐based porous frameworks (Figure i) …”
Section: Electrochemical Energy Storagementioning
confidence: 90%
“…Another promising strategy is to design porous polymeric frameworks with conducting properties as electrode materials for supercapacitors. The conductive frameworks enable the high utilization of the large surface area for electrical double layer capacitance and heteroatom effect (N) for pseudocapacitance, as has been found in aza‐fused CMPs (Figure g), triazatruxene‐based microporous polymers (Figure h), and triazine‐based porous frameworks (Figure i) …”
Section: Electrochemical Energy Storagementioning
confidence: 90%
“…As shown in the C1s core-level XPS spectra ( Figure S5a,c), PCMPs exhibited two peaks at~284.7 and~285.1 eV attributed to aryl C=C and C=N bonds; an additional peak at~287.5 eV assigned to C=O bonds of acetyl groups, respectively. [22,23] The N1s core-level XPS spectra of PCMPs ( Figure S5b,d) displayed the two peaks at~398.5 eV owing to pyridinic N. [15,22] All the information signifies that the desired structures of PCMPs are actually presented as suggested in Figure 1. Note that, replacing acetic acid with pyridine, asprepared PCMPs showed close wavenumber and chemical shift values ( Figure S4a Articles 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 tures.…”
Section: Resultsmentioning
confidence: 89%
“…The 3D skeleton structures of CMPs can induce the superior cycle ability of supercapacitors. [15] Furthermore, CMPs can be easily compounded with carbon materials to achieve higher electrical conductivity. [16] However, the applications of CMPs for supercapacitors still suffer from some problems.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the Fe 3 O 4 /RGO nanocomposite mentioned above was dispersed in the obtained solution by sonication to obtain Fe 3 O 4 @ZIF‐8/RGO. Finally, the electrode was obtained by dispersing Fe 3 O 4 @ZIF‐8/RGO in DMF and then casting onto a GCE electrode surface . The composite electrode was employed in a DA sensor and exhibited a favorable performance; the results showed that the composites combined the advantages of each constituent part.…”
Section: Chemical Sensorsmentioning
confidence: 99%